The Relationship between Limb Power with Distance Kick Soar-Far Using The Inner Feet Side in Carlos FC Football Club, Aceh Besar - Muzakir Muzakir; Junaidi Junaidi; Boihaqi Boihaqi (Universitas Serambi Mekkah, 2022)
This research is entitled: